The Prevalence of Dumping in International Trade: II - Viner, Jacob (Journal of Political Economy, 1922)
The export practices of other continental countries have not been subjected to as close or as critical examination as those of Germany, so that there is available but scanty material upon which to base conclusions as to the prevalence of dumping in these countries.But the combination of circumstances which especially favored the development of export dumping in Germany on a systematic and extensive scale, namely, the growth of large-scale manufacturing industries operating under unified or syndicated control and enjoying high tariff protection in the domestic market, were not present to nearly the same degree in the remainder of the Continent.In most of the continental countries manufacturing for export was either comparatively unimportant or was largely confined to the production by small concerns of individualized products under conditions not far removed from the handicraft stage.It is not to be expected, therefore, that dumping should be found to be as prominent in the export trade of these countries as of Germany.Such evidence as is available appears to justify the conclusion that in these countries dumping in the export trade was practiced on an extensive scale only by such producers as were operating under conditions closely similar to those governing the syndicated German industries, namely, large-scale machine industry, syndicated control, and a protected domestic market.In some respects conditions most closely resembling those of German manufacturing industry were to be found in Belgium.There were in this country many important large-scale manufacturing enterprises, organized into producers' syndicates closely modeled after the German kartells.But these syndicates exported so large a proportion of their total output, and the domestic market in many cases was relatively so unimportant, that there was little to be gained from an attempt to maintain domestic prices on a permanently higher level than those prevalent in the important export markets.Moreover, the Belgian tariff was too low, and the Belgian market too close to Germany, France, and England, to permit of the maintenance of prices in the domestic market substantially higher than the export prices-often dumping prices-of the producers in these countries.The conditions were in these important respects unfavorable, therefore, to the practice by Belgian producers of dumping on a systematic and substantial scale.'Some of the most important of Belgian industries nevertheless found it practicable to resort to dumping either intermittently or on a permanent basis, and in several instances export bounties, both to direct exporters and to domestic manufacturers buying materials for further use in manufacture for export, were employed.Among the industries which resorted more or less systematically to dumping were the iron and steel, coal, cement, plate glass, canned vegetables, and earthenware syndicates, all of them among the leading industries of Belgium.2Because the domestic market was relatively unimportant for some of these industries, Belgian dumping occasionally took the form of the sale of Belgian products at lower prices in distant foreign markets than in other export markets which were closer by and were "standard" markets for Belgian products.3I Cf.G. De Leener, L'Organisation Syndicale des Chefs d'Industrie, Brussels, I909, II, 274, 433.Cf. especially, p. 433: "La Belgique, a defaut de protection douaniere suffisante, present peu d'exemples caracterises de la pratique du 'dumping."' 2 For evidence of Belgian dumping, see U.